(untitled) (Journal of Economic Research & Business Administration, 2018)
Agriculture has been the most important branch of the economy of our country for many years, but, due to its specific features, for effective functioning it needs the all-round active support of the state. Without such support, the agrarian sector does not have the ability to dynamically develop and be competitive in the current market conditions, as many agricultural producers are not ready for them. This article examines the current situation of the agricultural sector in Kazakhstan. The main problems of financial support of agriculture at the state level have also been revealed.The results of this study can be applied by agricultural organizations and governing bodies when organizing measures to increase the effectiveness of state financial support for the agricultural sector.The study assessed the current level of budget financing of agriculture in Kazakhstan.With the help of economic methods of analysis the article analyzes the agricultural credit form of support, state support of insurance of risks in agriculture, the effectiveness of state programs aimed at improving current state of the agricultural sector.The conclusion is made that in the context of the globalization of socio-economic processes, the increase of efficiency and competitiveness of domestic agricultural production is impossible without strengthening state financial support for the agricultural sector of the economy.